Morphometric Measurements of Upper and Lower End of Dry Human Humerus - Siddique, Md Asraful Alam; Foysal, Abdullah Al; Phathan, Md Azmal Khan; Hasan, Abul; Karmakar, Pijush; Bristy, Priyanka Das (Journal of Brahmanbaria Medical College, 2026)
Background: The morphometric characteristics of the humerus are crucial in Forensic, Anatomy and Archaeology. These measurements can help forensic experts to estimate the age, sex and identity of an individual from skeletal remains. The goal of the current study was to examine various morphometric analyses of the humerus segment. Materials and methods: From January 2021 to December 2021, this descriptive type of study was carried out in the Anatomy Department at Sylhet MAG Osmani Medical College. For the study's purpose, 200 healthy adult right humeri were gathered. Samples that met the inclusion and exclusion criteria were used for data collection. the Vertical Diameter of the Head (VDH) the Transverse Diameter of the Head (TDH) the Maximum Transverse Diameter of the head (MTD) Epicondylar Breadth (EB) Condylar Breadth (CB) Breadth of the Capitulum (BC). All the variables were checked carefully. Data were analyzed and processed in windows 10 and SPSS version 23. Data were expressed as mean±SD. Results: The mean vertical diameter of the head of humerus was 42.28±3.43 mm, mean maximum diameter of the head of the humerus was 39.84±3.45 mm and mean transverse diameter was 39.42±6.29mm. In the lower end, the mean epicondylar breadth was 56.09±6.24 mm and mean condylar breadth was 40.42±3.35 mm. Conclusion: For anatomists, understanding of the morphometric measurements of humerus segments is crucial. It takes forensic specialists and archaeologists to identify a skeleton's identity. Additionally, it supports the surgeons during various humerus implantation operations. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 01 Jan 2025 ; 16-19